Kinerja Keamanan Dan Keselamatan Penerbangan Di Manouvering Area Bandara Udara Juwata Tarakan - Irfan, Irfan (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2019)
The existence of residential areas around the Juwata Tarakan airport results in the presenceof domestic residents, namely cattle entering the airport. Besides that, there is a communityaround the airport that crosses the runway. This condition can disrupt flight safety andsecurity at Juwata Tarakan Airport. In addition to explaining the impact caused by theobstruction (obstruction) the purpose of this study is also to maximize air traffic services,especially the aspects of aviation security and safety. The method used in this study is aqualitative research method while some data collection techniques are interviews,documentation and observation. Techniques and data analysis using qualitative descriptivemethods, namely by way of research and observations of obstruction (obstacles) that arearound Juwata Tarakan Airport. The results of the study are expected that the airportmanagement in Tarakan can provide socialization to the surrounding residents, increasesecurity and coordination, add communication tools and make a guardrail around the airportarea.